2021
DOI: 10.1007/s00484-021-02205-x
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the impact of heat on human physical work capacity; part III: the impact of solar radiation varies with air temperature, humidity, and clothing coverage

Abstract: Heat stress decreases human physical work capacity (PWC), but the extent to which solar radiation (SOLAR) compounds this response is not well understood. This study empirically quantified how SOLAR impacts PWC in the heat, considering wide, but controlled, variations in air temperature, humidity, and clothing coverage. We also provide correction equations so PWC can be quantified outdoors using heat stress indices that do not ordinarily account for SOLAR (including the Heat Stress Index, Humidex, and Wet-Bulb … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 57 publications
3
19
0
1
Order By: Relevance
“…Work rates: Fiala et al ( 2012 )’s thermoregulatory model was validated at a reference metabolic rate of 133 W m −2 , similar to the workload sustained in this study’s LightAmb condition. A compendium of studies recently conducted by Foster et al ( 2022a , 2022b ) showed the advantage that the UTCI had over other indices due to its direct inclusion of thermal radiation and wind movement in predicting heat stress, but these studies were geared toward work capacities nearing 30% VO 2max , well above the conditions of both of this study’s workload scenarios. This was also found in recent work by Ioannou et al ( 2022 ).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Work rates: Fiala et al ( 2012 )’s thermoregulatory model was validated at a reference metabolic rate of 133 W m −2 , similar to the workload sustained in this study’s LightAmb condition. A compendium of studies recently conducted by Foster et al ( 2022a , 2022b ) showed the advantage that the UTCI had over other indices due to its direct inclusion of thermal radiation and wind movement in predicting heat stress, but these studies were geared toward work capacities nearing 30% VO 2max , well above the conditions of both of this study’s workload scenarios. This was also found in recent work by Ioannou et al ( 2022 ).…”
Section: Discussionmentioning
confidence: 93%
“…We have demonstrated excellent validity and reliability of this experimental protocol (Cottle et al 2021 ). There was no solar radiation substitute or forced air movement inside the environmental chamber during experimental trials, though both do impact the human heat balance (Foster et al 2022a , 2022b ).…”
Section: Methodsmentioning
confidence: 99%
“…Black globe temperature, which is used to help determine the mean radiant temperature—one of the four fundamental environmental parameters that define a thermal environment—is often 10 to 15°C higher than the ambient (shaded) temperature in the middle of a clear summer day. The subsequent radiant heat load can exacerbate physiological heat strain and be detrimental to exercise performance 49 50. Moreover, as for heat stress,51–54 high levels of solar radiation, especially when directed towards the head, may also affect complex motor–cognitive tasks 55 56…”
Section: Section 1: Recommendations For Risk Mitigation By the Organi...mentioning
confidence: 99%
“…The production limit temperature for Holstein dairy cows has been reported to be 24 °C [2].WBGT represents the effect of heat on physical work capacity, and is used to assess heatstroke risk in humans [8]. A WBGT of 25 or mo re is considered highrisk for heatstroke, 28 or more is considered alarming, and 31 or more is considered dangerous [8]. WBGT has also been applied in thermal comfort studies of cattle [ 1 7].…”
Section: Discussionmentioning
confidence: 99%
“…The wet bulb globe temperature (WBGT) is used to assess the risk of heat stroke in humans [8]. Individuals in the median -based heat exposure category with the highest WBGT have a higher prevalence of heat -related symptoms than those in the lowest category, providing an indicator of the health effect of g lobal warming [7].…”
Section: Introductionmentioning
confidence: 99%